Sustaining Actor Engagement During the Opportunity Development Process. (24th October 2016) - Snihur, Yuliya; Reiche, B. Sebastian; Quintane, Eric
Abstract : Research summary : Recent entrepreneurship research has examined how opportunities are developed, highlighting the engagement of external actors. However, we know little about how entrepreneurs should interact with external actors to sustain their engagement. Since opportunity development is a process that unfolds over time, sustaining actor engagement is critical because it enables continued feedback and access to actors' resources. We present a process model that explains how entrepreneurs can sustain external actor engagement through two iterative phases: translation and transformation. We also propose that entrepreneurs can sustain actor engagement by structuring the timing of interactions and by modifying actors' perceptions of the time available for novel opportunity development. We conclude with an agenda for future research on actor engagement and entrepreneurs' temporal capabilities. Managerial summary : To develop business opportunities, entrepreneurs require support, feedback, and other resources from different groups of individuals (actors), such as customers, business partners, investors, and regulators. We explain how entrepreneurs should continue to interact with these actors throughout the development period to secure sustained access to resources. Entrepreneurs need to present the business opportunity to actors in an engaging way, and subsequently integrate the feedback received during development of the project. Sustaining engagement from actors involves an iterative process through which the business opportunity is communicated and transformed. Entrepreneurs can influence actors' engagement by choosing how and when to interact with them. We highlight time and actor feedback as important resources that can be used by skillful entrepreneurs to increase the odds of opportunity development success. Copyright © 2016 Strategic Management Society.